Response of Three Indigenous Pulse Crops to Different Moisture Conditions (University of Khartoum Journal of Agricultural Sciences, 2023)
A field experiment was conducted in the Demonstration Farmof the Faculty of Agriculture, University of Khartoum for two seasons(January to May 2005 and December 2005 to May 2006). The objectiveof the experiment was to study the effect of 7 and 14 days irrigationintervals on growth and yield of three local pulse crops; namely, Vignaunguiculata ‘Lubia Hilu’, V. sinensis ‘Lubia Kordofani’ and Lablabpurpureus ‘Lubia Afin’. The results showed that irrigation every 14 daysreduced dry matter production and seed yield, but increased thepercentage of crude protein in the seeds of the three crops as a result ofincrease in the ratio proteins: carbohydrates